Quantifying the dynamics of dislocation kinks in iron and tungsten through atomistic simulations. (May 2020) - Ji, Rigelesaiyin; Phan, Thanh; Chen, Hao; Xiong, Liming
Abstract: When high-Peierls-barrier materials such as iron (Fe) and tungsten (W) are deformed, dislocation kinks can be easily activated. The subsequent kink dynamics may dictate the dislocation mobility and the material's overall performance under certain conditions. In this work, taking the thermal-induced kink diffusion along ½<111> screw dislocation lines as an example, the kink dynamics in b.c.c. iron and tungsten are quantified through atomistic simulations. Results show that in both Fe and W, the kink dynamics, including its diffusion coefficient ( D kink ) and dissipation parameter ( γ kink ), are sensitive to the dimension (noted as L ) of a simulation cell size along the dislocation line direction: the larger L, the higher D kink, and the smaller γ kink . A scaling law for describing the three-stage L -dependent kink dynamics is extracted from a series of computational analysis of the kink diffusion along dislocations with L ranging from tens to hundreds of nanometers. It is found that, if a converged D kink is desired from atomistic simulations, the minimum L needs to be at least hundreds of nanometers. This is beyond the reach of an atomic-level model using a modest computational resource. To explain the L -dependent kink dynamics, we calculate the kink-induced local stress fields using two different atomistic stress formula, i.e., a widely-used Virial and a recently developed mechanical stress formula. Results suggest: (i) the L -dependent kink dynamics is caused by the long-range elastic interaction between the kink and its periodic images; and (ii) the Virial stress formula underestimates such interactions. This work lays the continuum description of kink-controlled dislocation dynamics on an atomistic foundation. It will also support the development of multiscale methods for addressing the coupled dynamics between the motion of a μm-long dislocation line and the atomic-level kink diffusion along the line itself in b.c.c. metals or other high-Peierls-barrier materials under deformation. Graphical abstract: Image 1 Highlights: The dynamics of kink diffusion along dislocation lines in two bcc metallic materials is characterized. The atomistic simulation cell size effect on the dislocation kink diffusion coefficient is quantified. The local stress near a kink and its contribution to the long-range kink-kink interaction are measured. A scaling law of describing the kink diffusion along the micrometer-long dislocation lines is calibrated. A link between MD, DD, and kMC simulations of kink-controlled dislocation dynamics is attempted.